STUDI KENYAMANAN UNTUK AKTIVITAS DI LANSKAP HUTAN KOTA UGM Studi Kasus: Klaster Agro UGM - Irwan, Siti Nurul Rofiqo; Kaharuddin, Kaharuddin (Fakultas Kehutanan UGM, 2010)
The phenomenon of glohal warming has caused discomfort activity in urban area. Greening in open space of Gadjah Mada University campus has been developed as urban forest landscape that supporting good environment produced high comfort jar activi(v and enhancing urban conservation. The research objectives were to observe the camfort.for activity in urban .forest landscape, to observe the canopy coverage of urban forest and to reveal the efFect of tree canopy coverage to the comfort for activity. Data collection was carried out by visual observation. questioner, micro climate measurement, and hemi!>pherical images of the tree canopy coverage. Data were analyzed by descriptive statistics. The tree canopy coverage was calculated hy the S!ky View Factor (SVF) of hemispherical images. Research results showed that activity ()pes in the urban forest landscape were study (10%), sitting (37%). meeting (39%), others (14%) at spread o,(sitting areas. Some factors that afrect the comfort for activity) in urban forest landscape were aesthetic, lower temperature, fresh air. inspirited area, and listened bird voice. The respondents (82,6%) said that the urban forest landscape was comfort for activity at whole time of07. 00- 17.00 by the condition of local climate presented by air temperature at 29. 7- 32. 6°C, normal hwnidit)' at 61.5-74.1% and breeze wind velocity at 0.6 - 2.8 mls. Tree canopv of urhan forest landscape had covered more than 50% identified by Sky view Factor (SVF 0. 026-0. 446). The tree canopy average of urhanforest created tree shaded areas for the activities which showed thermally comfort because of microclimate controlled by urban forest.